Analysis of the water flow in rectangular open channel flume with rectangular sharp crested weir - Muhammad Norkhuzairi, Shaharin (2013)
The sharp-crested weir is the most commonly used device in channels for flow measurement and flow regulation due to its simplicity. Several attempts have been made to study in detail the flow over different shapes of normal conventional weirs including those with sharp crest, side weirs and oblique weirs, mainly based on experimental work. On the contrary, little efforts have been done to use numerical models in investigating flow characteristic and pressure distributing over these types of weirs. The concern of this paper is to study flow over a rectangular sharp crested weir and to provide a means to estimate the discharge coefficient. A CFD Software which is ANSYS CFx-14 has been used for evolving a relationship to estimate the discharge coefficient for rectangular sharp crested weirs. Several combinations of discharge and weir height have been used to develop a best fit curve for estimating the discharge coefficient. The discharge coefficient estimate by the develop model has been found to be in good agreement with those listed in the literature within  4%error. The study showed that the important variable governing discharge over sharp crested weir was the water head over weir per weir divide by weir height, h/P. Furthermore, the advantages of an ANSYS CFX-14 as a tool for examining velocity vectors and pressure pattern over rectangular sharp crested weirs have been highlighted